MARKETING PUBLIC RELATIONS STRATEGY IN INCREASING CUSTOMER LOYALTY MS. GLOW STORE BANDUNG - Anggraeni, Gita; Cecep Safa’atul Barkah; Pratami; Arianis (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
The purpose of this research is to make or recommend a strategy for the MS Glow Store Bandung. The recommended strategy is the marketing public relations strategy to increase customer loyalty again, Ms. Glow Store Bandung. Customer loyalty is very important for the company because it has a big influence on the company, so a strategy to deal directly with customers is needed. This study used qualitative methods with interview techniques. The results of this study are that Ms. Glow Store Bandung can use marketing public relations strategies to increase customer loyalty. By using a pull strategy by promoting products via television or radio, a push strategy by holding promotions and price discounts, and a strategy pas by participating in social activities, as well as being balanced or accompanied by other marketing activities to increase customer loyalty.The purpose of this research is to make or recommend a strategy for the MS Glow Store Bandung. The recommended strategy is the marketing public relations strategy to increase customer loyalty again, Ms. Glow Store Bandung. Customer loyalty is very important for the company because it has a big influence on the company, so a strategy to deal directly with customers is needed. This study used qualitative methods with interview techniques. The results of this study are that Ms. Glow Store Bandung can use marketing public relations strategies to increase customer loyalty. By using a pull strategy by promoting products via television or radio, a push strategy by holding promotions and price discounts, and a strategy pas by participating in social activities, as well as being balanced or accompanied by other marketing activities to increase customer loyalty.